EFEKTIVITAS DANA DESA DALAM PENGEMBANGAN POTENSI EKONOMI DI GAMPONG PONDOK KEUMUNING KOTA LANGSA - Wali Munawar; Puti Andiny; Yani Rizal; Safuridar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to evaluate the effectiveness of village fund management in Gampong Pondok Keumuning from the perspective of the village community. Data were analyzed to determine the percentage of effectiveness of overall village fund management, fund management towards village potential development, and the level of community participation in village fund management. The results of the study indicate that according to the views of the Gampong Pondok Keumuning community, village fund management by the village government has been effective with a percentage of 76.40%. Overall village fund management received a total index value of 67.06%, which indicates an effective category. The village fund budget for village potential development was also considered effective with a score of 74.22%.